(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The aim of this study was to analyze cybersecurity in accounting information systems and its impact on protecting sensitive financial data of Libyan industrial companies. This was achieved by understanding the concept of cybersecurity analysis. To achieve these goals, the descriptive analytical method was adopted by reviewing books, journals, research papers, and available online resources that serve the study’s purposes. The descriptive analytical approach was used to analyze the data and extract results using the SPSS statistical analysis program. The researchers used a questionnaire to gather the necessary data for this study, distributing 25 questionnaires, with 22 returned, representing an 88% response rate. After review, the questionnaires were found to be valid for statistical processing. The study population consisted of all employees of the financial management department at the Al-Marqab Cement Factory, where a comprehensive survey of the entire sample was conducted. The study reached several conclusions, the most important being that cybersecurity analysis affects the protection of sensitive financial data in accounting information systems, and access control policies impact the security of sensitive financial data. Additionally, the effectiveness of incident response strategies is not determined or measured when a data breach occurs at Al-Marqab Cement Factory. The study concluded with several recommendations, the most important of which include: the need to define and measure the effectiveness of incident response strategies during data breaches, organizing workshops and training programs for employees on the importance of cybersecurity analysis and its impact, and conducting a comprehensive assessment of the cyber risks facing accounting information systems in industrial companies. Risk analysis tools can be used to identify potential vulnerabilities.